HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI REMAJA DENGAN SIKAP PENCEGAHAN KEHAMILAN PRA NIKAH DI SMA 10 HALMEHARA TIMUR - Vidayati, Lelly Aprilia; Wijiastutik, Vivin; Hayati, Ida (Jurnal Ilmiah Maternal, 2025)
ABSTRACK. Teenage pregnancy aged 11-19 years in recent decades has become a health problem (WHO). Based on the results of a preliminary study on adolescent attitudes in preventing premarital sex, it was found that 40% had a positive attitude and 60% had a negative attitude. The purpose of this study is to see the relationship between adolescent reproductive health knowledge and premaritality pregnancy prevention attitudes. This type of research is correlative analytic of cross sectional design. The Independent variable is reproductive health knowledge and the Dependent variable is the attitude of premarital pregnancy prevention.. The population was 140 with a research sample of 128 respondents. The sampling technique uses proportional random sampling, the research was carried out in classes X and XII of SMA 10 East Halmahera Regency on December 1, 2024. The research instrument used a questionnaire, using the chi-square statistical test. From the research results, there is good knowledge, while the attitude towards premarital pregnancy prevention is positive at 70.4%, and reproductive health knowledge is sufficient with a negative attitude towards premarital pregnancy prevention at 68.1%. The chi-square statistical test results obtained a p-value of 0.00 (p ≤ 0.05), thus Ho is rejected and Ha is accepted, meaning there is a significant relationship between adolescent reproductive health knowledge and attitudes towards preventing premarital pregnancy at SMA 10, East Halmahera Regency. It is hoped that school agencies and health centers will provide Adolescent Reproductive Health counseling at least 2 times in 1 year to increase adolescent knowledge. Keywords: Adolescents, Reproductive Health, Premarital Pregnancy